The Natural Selection of Private and Inner Speech - O’Connor, Sean (Frontiers in Psychology, 2020)
This article analyzes the emergence of private and inner speech from the perspective of natural selection, arguing that social speech acts as a selection pressure for the emergence of private speech, that private speech acts as a selection pressure that leads to the emergence of inner speech, and that this view of private and inner speech may help to explain the natural selection of a variety of other traits of the human mind in an asymmetric intraspecific evolutionary arms race.